2022
DOI: 10.3389/fpsyg.2022.870392
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Anxiety Assessment: The Psychometric Properties of the Polish Version of the Climate Anxiety Scale

Abstract: The Climate Anxiety Scale (CAS) is a 13-item questionnaire for assessing climate anxiety (CA) as a psychological response to climate change. The CAS consists of two subscales, namely, cognitive impairment and functional impairment. This study aimed to validate the Polish version of the CAS. The sample included 603 respondents (344 females, 247 males, and 12 non-binary), aged 18–70 years (M = 25.32, SD = 9.59). Based on the exploratory factor analysis results, we proposed a 3-factor solution (i.e., intrusive sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 28 publications
9
35
2
Order By: Relevance
“…40 A gender difference was not found in the CCAS 15 in terms of cognitive-emotional impairment or functional impairment, but for behavioural engagement women reported higher levels than men. In Wullenkord, 49 compared to men, women reported higher levels of climate change anxiety (overall score); while Larionow 45 found that women had higher cognitive impairment and functional impairment in CCAS. Testing the validation of CCAS in four countries, Tam 48 revealed that men in China and the US had higher levels of cognitive impairment and functional impairment, as compared to women.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…40 A gender difference was not found in the CCAS 15 in terms of cognitive-emotional impairment or functional impairment, but for behavioural engagement women reported higher levels than men. In Wullenkord, 49 compared to men, women reported higher levels of climate change anxiety (overall score); while Larionow 45 found that women had higher cognitive impairment and functional impairment in CCAS. Testing the validation of CCAS in four countries, Tam 48 revealed that men in China and the US had higher levels of cognitive impairment and functional impairment, as compared to women.…”
Section: Resultsmentioning
confidence: 94%
“…Bowler and Schwarzer’s study 38 had high risk of bias. Four validation studies of CCAS 45,4547,49 had moderate risk of bias. One validation study of HEAS had moderate 54 and one had high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…The four climate anxiety items included on the YDI survey were drawn from both factors (i.e., cognitive-emotional impairment and functional impairment) of the original CCAS. This study adds to the growing body of literature that aims to validate the CCAS in different populations (Larionow et al, 2022;Mouguiama-Daouda et al, 2022;Wullenkord et al, 2021); however, to our knowledge, no attempts to shorten the scale have been conducted yet.…”
Section: Discussionmentioning
confidence: 99%
“…An additional benefit in establishing cross-cultural measures is to facilitate examination of whether any groups are more vulnerable to these psychological effects of climate change than others. For example, young people are thought to be more susceptible to experiencing climate anxiety (US [ 8 ]; Poland [ 32 ]), though Hogg et al’s [ 9 ] Australian research found that older participants reported higher rumination, while younger participants reported higher personal impact anxiety, and there was no relationship between age and experiences of affective and behavioural symptoms. This indicates that more research is needed on eco-anxiety’s associations with age.…”
Section: Introductionmentioning
confidence: 99%